Perspectives on bond lending and specialness - Lars Jul Hansen; Stig Hesselberg; Louise Mogensen (Danmarks Nationalbank, 2005)
This working paper provides a basic introduction to bond lending and reviews the main results from the academic literature. These results are compared with actual price data on bond lending from the US and European markets for the period from 3 March 2003 to 14 May 2004. Three specific issues regarding bond lending are subsequently discussed. Firstly, the differences between the markets for securities lending in the US and in Europe are explored and a number of factors that explain this difference are identified. Secondly, cyclical movements in the prices for borrowing bonds are explored. Thirdly, the relationship between liquidity and bond lending is reviewed. The last part of the working paper discusses investment strategies to exploit the structural relationships in the bond lending market.
Keywords: 330; Repo-Geschäft; Repo-Geschäft; USA; Europa